PENGARUH MODAL KERJA TERHADAP RETURN ON ASSET (ROA)PADAPT HOTEL SAHID JAYA INTERNASIONAL, Tbk (STIE Rajawali Purworejo, 2018)
The purpose of this study is to find out how much influence Working Capital Turnover is limited to Cash Turnover, Turnover Turnover and Inventory Turnover to increase Return On Assets (ROA) generated by the company and know which among the three variables that give the most dominant influence on Retutn On Asset. The data used is secondary data derived from the financial statements of PT. Sahid Jaya International Hotel, Tbk registered in Indonesia Stock Exchange period 2011-2016 obtained through Indonesia Stock Exchange (IDX). Data analysis techniques in this study using multiple correlation analysis, multipleregression, t test, f test and coefficient of determination and using tools computer program Statisrical Product and Services Solution (SPSS) version 16. The results of analysis based on calculations using correlation test relationship between ROA variable with cash turnover of 0.663.Sementara correlation between ROA variable with receivable turnover is equal to-0.057.Kemudian correlation between ROA variable with large inventory turnover of both relationship is -0.444. In the multipleregression test the following equation is obtained: Y =-3,243 + 0,170 X1-0,040 X2 + 1,273 X3. From the t test results obtained partially no positive and significant effect between cash turnover variables on ROA (Return On Asset), partially no positive and significant influence between cash rotation variables to ROA, partially no positive and significant influence between variable receivables turn over to ROA, partially there is no positive and significant influence between variable inventory turnover to ROA, and simultaneously there is no positive and significant influence between variable cash turnover, receivable turnover, and inventory turnover of ROA. The magnitude of the coefficient of determination is 0.658 or equal to 65.8%. In this research ROA at PT Sahid Jaya International Tbk has unstable performance, due to ROA of PT Sahid Jaya International Hotel, Tbk each year experience increase and decrease profit and cash turnover, receivable turnover and inventory turnover not directly affect on ROA.